Notes towards a Definition of Adaptive Reuse - Sally Stone (Architecture, 2023)
This essay will discuss the evolution of writings about adaptive reuse. The architectural practice is as old as the buildings themselves, yet it has scarcely been discussed or even recognised until relatively recently. The essay will document the varied influences that informed the early publications (the first from 1976). The lack of easily available material (that is, books and documented buildings) meant that pioneering writers had to draw upon other sources—those beyond established architectural discussions. Therefore, these early authors were not limited by the strictures of an already established subject but were able to collate information from a variety of sources. Thus, adaptive reuse draws upon a collage of different sources, many beyond pure architecture, including installation art, fine art, curation, interior design, and urban design. Inevitably, as the subject moves from the periphery of architectural practice towards the middle ground, the number of publications has increased. This diversity has provided the subject with a greater scope, supporting the acknowledgement of the importance of technology, sustainability, and conservation in addition to ideas of heritage and culture, while also allowing for a much less Western-centric focus.